2015
DOI: 10.3892/etm.2015.2710
|View full text |Cite
|
Sign up to set email alerts
|

Association between toll-like receptor 6 expression and auxiliary T cells in the peripheral blood of pediatric patients with allergic purpura

Abstract: Abstract. The aim of the present study was to investigate the correlations between toll-like receptor 6 (TLR6) expression in the peripheral blood mononuclear cells (PBMCs) and auxiliary T cells of children with purpura. A total of 42 children with acute Henoch-Schönlein purpura (HSP) were selected for the study, and a further 30 healthy children were selected as a control group. Enzyme-linked immunosorbent assays were performed to detect the levels of plasma interferon (IFN)-γ, interleukin (IL)-4 and IL-17, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Subsequently, 4 conference abstracts and 16 studies with no data of interest were excluded, at last, with 25 articles included in the present meta-analysis. [2,13,14,21–43] Among all the included studies, 24 were retrospective studies and 1 were case-control analysis. The main baseline characteristics of the included publications are at length provided in Table 1 and Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 4 conference abstracts and 16 studies with no data of interest were excluded, at last, with 25 articles included in the present meta-analysis. [2,13,14,21–43] Among all the included studies, 24 were retrospective studies and 1 were case-control analysis. The main baseline characteristics of the included publications are at length provided in Table 1 and Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…As studies have shown, infection is the most common cause of HSP, and about 40%-70% of children are mainly affected by respiratory tract infection [25][26] .Ma et al [17] showed that the increase of WBC was one of the independent risk factors for HSPN (P < 0.05). Chang et al [27][28] believed that the mechanism may be tissue damage caused by in ammatory mediators secreted by neutrophils, resulting in swelling and necrosis of renal vascular endothelium, while activated substances such as oxygen free radicals can chemotactic more WBC, aggravate vascular injury and form a vicious circle. EBV belongs to the γ subfamily of Herpesviridae, which is a linear double-strand DNA virus, and human is its only natural host.…”
Section: Discussionmentioning
confidence: 99%
“…[22,23] Ma et al [16] showed that the increase of WBC was one of the independent risk factors for IgAVN (P < .05). Chang et al [24,25] believed that the mechanism may be tissue damage caused by inflammatory mediators secreted by neutrophils, resulting in swelling and necrosis of renal vascular endothelium, while activated substances such as oxygen free radicals can chemotactic more WBC, aggravate vascular injury and form a vicious circle. EBV belongs to the γ subfamily of Herpesviridae, which is a linear double-strand DNA virus, and human body is its only natural host.…”
Section: Discussionmentioning
confidence: 99%